2021
DOI: 10.21037/atm-20-6514
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of hyperthermic intrathoracic chemotherapy for advanced lung cancer

Abstract: The traditional treatment of stage IV lung cancer is predominantly supportive or palliative. No current standardized guidelines promote the use of hyperthermic intrathoracic chemotherapy (HITHOC) in the treatment of advanced lung cancer with pleural involvement. Several small studies have examined the safety and utilization of HITHOC for this population, though the data is extremely limited. A review of the literature is presented in accordance with the Narrative Review checklist. The MEDLINE electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Not only distant metastatic lesions, but other factors such as concurrent intrathoracic metastatic lesion should also be considered. Recent studies show diverse clinical approaches in advanced NSCLC such as primary tumor resection, hyperthermic intrathoracic chemotherapy in patients with malignant pleural effusion, [50][51][52] and future studies that take various host and tumor-related factors into account are vital.…”
Section: Discussionmentioning
confidence: 99%
“…Not only distant metastatic lesions, but other factors such as concurrent intrathoracic metastatic lesion should also be considered. Recent studies show diverse clinical approaches in advanced NSCLC such as primary tumor resection, hyperthermic intrathoracic chemotherapy in patients with malignant pleural effusion, [50][51][52] and future studies that take various host and tumor-related factors into account are vital.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the local antitumor effects, these agents can also cause pleurisy, pleural adhesions, and pleurodesis, thus reducing the likelihood of pleural effusion recurrence. 11 Other agents that have been studied include carboplatin and bleomycin, with some investigators also combining multiple chemotherapeutic agents to enhance treatment effects due to synergistic effects of the drugs. In a large meta-analysis that accumulated data from 13 randomized controlled trials, authors demonstrated that the combination of endostatin (a novel recombinant human endostatin that blocks vascular endothelial growth factor [VEGF]) with chemotherapy showed a better overall response rate (ORR) that chemotherapy alone in patients with malignant pleural effusions secondary metastatic cancer (breast, lung, digestive tract).…”
Section: Intrapleural Anticancer Therapy For Malignant Pleural Diseasesmentioning
confidence: 99%
“…10 The most commonly studied agent has been cisplatin as an intraoperative adjuvant therapy in malignant pleural mesothelioma. 11 The rationale for this approach is the ability to deliver cytotoxic agents in concentrated doses locally with reduced systemic absorption and toxicity. In addition to the local antitumor effects, these agents can also cause pleurisy, pleural adhesions, and pleurodesis, thus reducing the likelihood of pleural effusion recurrence.…”
Section: Intrapleural Anticancer Therapy For Malignant Pleural Diseasesmentioning
confidence: 99%
“…Advancement in targeted therapy and immunotherapy may eliminate the need for P/D and HITEC altogether for Stage IV NSCLC with PD only in the future. 27 Aggressive trimodality treatment approach has been evaluated in patients with secondary pleural metastasis. 15,16 This combination has been effective in achieving local control and improved 5-and 10-year survivals in selected patients with metastatic thymic malignancies.…”
Section: Thymic Cancermentioning
confidence: 99%